Effectiveness of a group and brochure psychoeducation intervention to improve depression level and treatment continuity among adults with depression in turkey: A controlled study. - (:unkn) unknown (ALLIED ACAD, 2017)
Purpose: The current study examined the efficacy of a group and brochure psychoeducation intervention for improving levels of depression among patients with a depressive disorder. Methods: This study is a semi-experimental with a pre-test, post-test, control group and follow-up. The sample of this study consisted of patients with depression (n=153). Based on their scores in depression inventory, the patients were divided into three groups. The groups received Continuity Enhancement Treatment for Antidepressants (CETA) with form of group and brochure. The psychoeducation and brochure groups both received psychoeducation and antidepressant treatment. The control (CG) group not received a psychoeducation and only continued antidepressant treatment. The Personal Information Form and Beck Depression Inventory (BDI) were used. Results: When the scores of the depressed patients in the experimental groups and control group were compared at the pre-test, posttest and 3 and 6 months follow ups, a significant difference was only found in BDI post-test scores. Conclusion: Group and brochure psychoeducation included CETA program was effective for improving antidepressant adherence. Psychoeducational approaches to be applied by psychiatry nurses to outpatients who received diagnosis of depression for the first time were also considered as cost-effective methods.
Keywords: Depression; Adherence; Cost-effectiveness; Measurement; Antidepressants; CONTROLLED-TRIAL; PRIMARY-CARE; DISORDERS; PROGRAM; EFFICACY; COST